Зарубежный опыт использования метана исходящего воздуха шахт - Кауфман, Л.Л.; Лысиков, Б.А.; Лабинский, К.Н. (Физико-технические проблемы горного производства, 2007)
Представленo закордонний досвід перетворення метану, що викидається в атмосферу виходячої струї вентиляції шахт, в джерело енергії. Показано позитивні результати випробувань та промислові зразки обладнання даної проблеми. Foreign experience of conversion of the methane from outgoing airstream of mine ventilation to the energy is shown in this article. Positive results of the testing and the industrial models of the equipment are represented.